Optimizing Land-Use Scenarios for Water-Resource Sustainability in the Upper Kampar Watershed, Indonesia - Firman Hidayat; Agung Primatara Marwan (Universitas Panji Sakti, 2026)
Soil erosion in the Upper Kampar Watershed threatens reservoir storage and downstream water reliability. This study compared four land-use scenarios using the Universal Soil Loss Equation and the Soil Conservation Service Curve Number method across 100 land units. Existing land use produced 142.70 t.ha−1.yr−1 of soil loss, well above the tolerable value of 39.62 t.ha−1.yr−1. Meeting the minimum forest-cover rule lowered erosion by 31.95% but did not reach the threshold. Strip cropping reduced erosion to 32.90 t.ha−1.yr−1, whereas rehabilitation of mapped protected areas yielded 36.15 t.ha−1.yr−1 and the lowest Qmax/Qmin ratio (28.38). Discharge records supported directional checking, but independent event-scale validation was unavailable. The results support protected-area rehabilitation as a zoning framework, combined with soil-conservation practices on cultivated slopes and field monitoring of sediment and river flow.